“The Analysis and the evaluation of the qualitative characteristics of surface water in the "Shabala" valley basin in Al-Anbar Governorate” - et. al., Ahmed Abbas Khalaf Al-Halboosi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The quality of water varies according to its location in the basin, as the geological conditions, topography and climatic a prominent role in determining the quality of water and the extent to which it can be used by humans for various purposes. It is located between latitude (34 ° 30'37 ") and (34 ° 49'38") north and between longitude (41 ° 39'3 ") and (41 ° 52'17") east, As for the location of the spatial study area, it is located within Al-Anbar Governorate, it is bounded on the north by the Valley of Al-Tayyarat and on the east by the Valley of Al-Safia, while on the south it is bordered by the Euphrates River, and by the Valley of Al-Aquod to the west, and its area is (356) km2. The results of the evaluation showed that all surface water samples located to the north of the study area are not suitable for human drinking, which are represented by samples (S1, S2, S3, S4, S5, S6) because they do not conform to the internationally approved specifications, As a result of the high concentration of salts in it. While the results of the samples located south of the study area are within the specifications, they can be used for human drinking as well as for other uses.